Living Standard of Population in Uzbekistan - Fazlitdin Bahadirovich Aminov (Scientific Trends, 2023)
The article examines Uzbekistan's poor situation as well as solutions. The author's research on the degree of poverty in the Republic of Uzbekistan is presented in this article, which also explores the reasons, various groups of poverty, and various definitions of poverty as well as its causes and prevalence in the Republic. The examination of the key metrics defining the nation's current socioeconomic situation has been completed. Ways to fix the issue are suggested based on the conclusions reached.
Keywords: poverty level, approaches to the definition of poverty, socio-economic state of the country, ways to solve the problem, reforms, unemployment, social instability, standard of living of the population.